Mahasiswa di Era Pandemi Covid-19: Apakah Mungkin Kuliah Sambil Berbisnis? - Genesis Sembiring Depari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
The COVID-19 pandemic has affected all aspects of human life. This influence can be in the form of a positive or negative impact. Among students, not a few negative effects have been felt, such as decreased learning outcomes, increased boredom and stress etc. In addition to the negative impacts, some positive impacts can be seen and felt. One of them is the increasing ability of the community to use and utilize internet technology such as video conferencing technology, the use of social media etc. With the increasing ability to use internet technology, the opportunities to market products or services through the internet are also increasing. So that it brings new opportunities for students to be able to start their entrepreneurial activities from an early age when they are still studying in college. This community service activity is carried out through a scientific webinar that focusing on ways and strategies for students to be able to start their business as early as possible in the era of the COVID-19 pandemic. Participants in this community service activity consist of management study program students and the public.